"I Quit": Testing the Added Value and Sequencing Effects of an Efficacy-focused Message among Cigarette Warning Labels. Issue 5 (3rd May 2020) - Jesch, Emma; Niederdeppe, Jeff; King, Andy J.; Safi, Amelia Greiner; Byrne, Sahara
Abstract : Many emotional appeal theorists argue that negative affect and efficacy work together to promote adaptive behavioral responses to a threat, yet most research on cigarette warning label messages has not examined the intersection between negative affect, hope, and efficacy. The current study tests effects of exposure, at different points in a sequence, to an efficacy-focused warning label in the context of threat-focused warning labels. We conducted an online, between- and within-subjects experiment with 398 adult smokers, testing the effects of warning label exposure on negative affect, hope, efficacy beliefs, and intentions to quit. Exposure to the efficacy-focused "Quit" label aroused higher levels of reported hope and lower levels of reported negative affect than threat-focused labels. Negative affect increased with each additional exposure to a threat-focused warning label, regardless of the order in which respondents saw the "Quit" label. Exposure to the "Quit" label (within a larger set of three threat-focused labels) led to greater self-efficacy but did not influence response efficacy or intentions to quit. We conclude that "Quit" messaging on warning labels can inspire both hopeful feelings and efficacy beliefs. Future research should identify the optimal balance between threat-focused and hopeful quit messages.